Novel approaches for the lipid sponge phase crystallization of the Rhodobacter sphaeroides photosynthetic reaction center. (2020) - Selikhanov, Georgii; Fufina, Tatiana; Vasilieva, Lyudmila; Betzel, Christian; Gabdulkhakov, Azat
No abstract available